Information disclosure in credit markets when banks’ costs are endogenous - Van Tassel, Eric (Journal of Banking & Finance, 2011)
In this paper we develop a model of information disclosure among banks based on an endogenous interest rate for externally placed debt. Banks with private credit information are given an opportunity to disclose information prior to competing for borrowers. While disclosure eliminates a bank’s information advantage over its competitors, disclosing information creates a new advantage for the bank in terms of a lower cost of external funds. We find that the incentive for a bank to disclose information is inversely related to the bank’s capital ratio and positively related to the number of other banks that disclose information.